Validation of The Kansas Marital Satisfaction Scale In an Indonesian Context - Endah Puspita Sari; Avin Fadilla Helmi; Arum Febriani (Green Publisher, 2025)
As Indonesian researchers are increasingly interested in studying the psychology of marriage and family psychology, the need for tools that can assess marital satisfaction becomes important. This is because marital satisfaction is the most widely studied research topic. The results of the study and the findings of the review found that the Kansas Marital Satisfaction Scale (KMSS) is a robust instrument. This study aimed to adapt the Kansas Marital Satisfaction Scale and to demonstrate its construct validity. The participants included 330 millennials who were either husbands or wives in heterosexual marriages (128 husbands and 202 wives with M-marriage age = 25.33 and SD-marriage age = 3.12). The findings indicated that the unidimensional model and the just-identified model with high factor loading (?2 = 0.000; df = 0; RMSEA = 0; CFI = 1.000; TLI = 1.000), are consistent with previous research. The omega reliability obtained for the Indonesian version of KMSS was 0.946. This article provides a detailed description of the instrument’s adaptation and validation process. The findings of this study support the developer of the KMSS, asserting that the Indonesian version of the KMSS is a brief yet valid and reliable instrument for measuring marital satisfaction, making it suitable for both practical applications and scientific research.